The Development of Forklift Ordering Management Systemfor Siam Industrial Complete.Co.,Ltd. (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
The purposes of the research were to 1) develop a forklift ordering management system for Siam industrial Complete.co.,ltd. and 2) evaluate the user’s satisfaction of forklift ordering management system for Siam industrial Complete.co.,ltd.. This system was developed based on System Development Life Cycle (SDLC). The forklift ordering management system as web application by PHP and MySQL. The sample of this study consisted of 1) three experts in information systems development, 20 purposive sampling members and staff who used the system. The research instruments were 1) quality assessment questionnaire, and 2) satisfaction questionnaire. Data were analyzed through statistics including mean and standard deviation (SD). The research founding showed the results of the performance evaluation by 3 experts, which is a test of the overall functioning of the system. It was found that in the overall the system that has been developed has a high level of efficiency with a mean of 4.46 and a standard deviation of 0.57 and statistical of user the system from 20 users, it was found that system. users were satisfied with the developed system. in a level of efficiency with a mean of 4.45 and a standard deviation of 0.60. In conclusion, these forklift ordering management system works effectively, and meet the stated objectives.